(untitled) (Contemporary Mathematics, 2023)
In this paper, we introduce and investigate the neighborhood of binary self-dual codes. We prove that there is no better Type I code than the best Type II code of the same length. Further, we give some new necessary conditions for the existence of a singly-even (56,28,12)-code and a doubly-even (72,36,16)-code.